A DNA Spiegelmer to staphylococcal enterotoxin B - Purschke, Werner G. (Oxford University Press, 2003)
Bacterial staphylococcal enterotoxin B is involved in several severe disease patterns and it was therefore used as a target for the generation of biologically stable mirror-image oligonucleotide ligands, so called Spiegelmers. The toxin is a 28 kDa protein consisting of 239 amino acids. Since the full-length protein is not accessible to chemical peptide synthesis, a stable domain of 25 amino acids was identified as a suitable selection target. DNA in vitro selection experiments were carried out against the equivalent mirror-image d-peptide domain resulting in high affinity d-DNA aptamers. As expected, the corresponding enantiomeric l-DNA Spiegelmer showed comparable binding characteristics to the l-peptide domain. Moreover, the Spiegelmer bound the whole protein target with only slightly reduced affinity. Dissociation constants of both peptide–oligonucleotide complexes were measured in the range of 200 nM, whereas the Spiegelmer binding to the full-length protein was determined at ∼420 nM. These data demonstrate the possibility to identify Spiegelmers against large protein targets by a domain approach.